Bevacizumab synergises with the BCL 2 inhibitor venetoclax to effectively treat B‐cell non‐Hodgkin's lymphoma. (3rd July 2019) - Wang, Li; Peng, Shaoyong; Sun, Weipeng; Liu, Xiaoxia
Abstract: Objectives: Our present study has shown a potential role for VEGF‐A‐mediated autocrine signalling to promote survival and proliferation of SU‐DHL‐6 cells, but the cells could not undergo apoptosis but rather decrease proliferation after bevacizumab treatment. Therefore, we would like to further study the antitumour efficacy of venetoclax (BCL2 inhibitor) in combination with bevacizumab in B‐cell NHL. Methods: The human cytokine antibody array, RT‐qPCR, Western blot, ELISA, apoptosis assay and xenografted mouse model et al were used. Results: We described a unique phenomenon that SU‐DHL‐6 cells showed cell density‐dependent survival and growth. Then, we suggested the expression of VEGF‐A was positively correlated with the cell density using a human cytokine antibody array and indicated an important role of VEGF‐A in the survival and proliferation of SU‐DHL‐6 cells. Additionally, xenografted SU‐DHL‐6 cells formed tumours in mice that grew in response to VEGF stimulation. GEO data set also suggested that high VEGF‐A expression reflected poor prognosis. The combination therapy with bevacizumab and navitoclax could significantly induce of cell death in vitro and reduce the tumour size and weight with well tolerated in vivo. Conclusions: Our findings propose a novel combined strategy in which bevacizumab synergises with the BCL2 inhibitor venetoclax that is effective against B‐cell NHL.